PENERAPAN MODEL PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 3 BUDONG-BUDONG KABUPATEN MAMUJU TENGAH - Yanti, Sarmila; Mustamin; Raehana, Syarifa; Bunyamin, Andi; Hasriani, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on the results of classroom action research that has been carried out for two cycles, it can be concluded that the application of the Scramble learning model is able to improve student learning outcomes in the subject of Islamic Religious Education for class VIII.A at SMP Negeri 3 Budong-Budong, Central Mamuju Regency. This improvement can be seen from the increase in student learning activities during the learning process, which is shown through activeness in discussions, working together, composing sentences, and presenting the results of group work. In addition, student learning outcomes also experienced a gradual increase, marked by the percentage of learning completeness increasing from 30% in the pre-cycle, to 60% in cycle I, and reaching 90% in cycle II, with the average class value increasing from the initial condition to 87.33 in cycle II. These results indicate that the research success indicator has been achieved, namely more than 80% of students obtained scores above the Minimum Completion Criteria (KKM) of 75. Thus, the Scramble learning model is proven to be effective in Islamic Religious Education learning because it is able to create an active, fun, collaborative learning atmosphere, and improve student understanding and learning outcomes.